Inadequate Self-Efficacy in Health: A Conceptual Analysis - Isabela Mendonça Rodrigues dos Santos; Diogo Matheus Barros da Silva; Maria Neyrian de Fatima Fernandes; Francisco Mayron Morais Soares; Isaura Leticia Tavares Palmeira Rolim (Aquichan, 2026)
Introduction: Self-efficacy is a psychological construct developed by Bandura that is widely used in the health sciences; it refers to an individual’s belief in their ability to organize and perform the actions necessary to cope with future situations. In contrast, although inadequate self-efficacy is often described as a limited individual perception, it remains relatively undefined in the literature. Objective: To conduct a conceptual analysis of the term ‘inadequate health self-efficacy, focusing on its applicability in the nursing context. Materials and Methods: This is a conceptual analysis based on the eight steps proposed by Walker and Avant, complemented by an integrative literature review, following the guidelines of the PRISMA checklist. The search was conducted during June 2025 in the SciELO, PubMed, and EBSCO databases, using the keyword ‘inadequate health self-efficacy,’ with no language restrictions and a time frame limited to the last five years. Eligibility criteria included original articles, theoretical or methodological studies, and reviews that directly or indirectly addressed the concept of inadequate health self-efficacy, available in full. Results: Inadequate health self-efficacy is an individual’s limited belief in their ability to take the necessary actions to achieve therapeutic goals and maintain self-care behaviors, resulting in emotional, functional, and clinical impairments. Furthermore, precedents (chronic condition, lack of knowledge, and lack of social support) and consequents (poor treatment adherence, clinical deterioration, and psychoemotional distress) were identified. Conclusion: This conceptual evolution will contribute significantly to evidence-based nursing practices informed by clinical judgment, which will strengthen approaches aimed at promoting patient self-care and autonomy.